Veterinaty specializations of secondary importance. Computer technology. Β. Application and use in medicine and related sciences - ΧΑΤΖΗΟΛΟΣ, ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Because of the tremendous importance of computers in medicine, their use is discussed in detail, under general practice; medical information systems for research in diagnosis and treatment; patterns of clinical care; clinics and hospitals; and various laboratories of related medical fields, including applied sciences, physical and chemical sciences, and radioimmuno-assays. As far as the use of computers in nuclear medicine is concerned, a description is given of the cross-section X-ray technique, known as the computerized axial tomography (CAT), and used for detection and radiation treatment of malignant tumors, as well as for the inspection of the coronary arteries for the early detection of lesions in their walls and thus contributing to the prevention of heart attacks. In view of the advantages of this method and the significant advances in veterinary medicine that it may presage, reference is also made to experiments conducted with a modified CAT method adapted for use on movings organs, such as the heart of laboratory animals. Finally, computer development during the last few decades is briefly reviewed